Global Differences in Risk Factors, Etiology, and Outcome of Ischemic Stroke in Young Adults—A Worldwide Meta-analysis: The GOAL Initiative. (8th February 2022) - Jacob, Mina A.; Ekker, Merel S.; Allach, Youssra; Cai, Mengfei; Aarnio, Karoliina; Arauz, Antonio; Arnold, Marcel; Bae, Hee-Joon; Bandeo, Lucrecia; Barboza, Miguel A.; Bolognese, Manuel; Bonardo, Pablo; et al.
Abstract : Background and Objectives: There is a worldwide increase in the incidence of stroke in young adults, with major regional and ethnic differences. Advancing knowledge of ethnic and regional variation in causes and outcomes will be beneficial in implementation of regional health care services. We studied the global distribution of risk factors, causes, and 3-month mortality of young patients with ischemic stroke, by performing a patient data meta-analysis from different cohorts worldwide. Methods: We performed a pooled analysis of individual patient data from cohort studies that included consecutive patients with ischemic stroke aged 18–50 years. We studied differences in prevalence of risk factors and causes of ischemic stroke between different ethnic and racial groups, geographic regions, and countries with different income levels. We investigated differences in 3-month mortality by mixed-effects multivariable logistic regression. Results: We included 17, 663 patients from 32 cohorts in 29 countries. Hypertension and diabetes were most prevalent in Black (hypertension, 52.1%; diabetes, 20.7%) and Asian patients (hypertension 46.1%, diabetes, 20.9%). Large vessel atherosclerosis and small vessel disease were more often the cause of stroke in high-income countries (HICs; both p < 0.001), whereas "other determined stroke" and "undetermined stroke" were higher in low and middle-income countries (LMICs; both p < 0.001). Patients in LMICs were younger, had less vascular risk factors, and despite this, more often died within 3 months than those from HICs (odds ratio 2.49; 95% confidence interval 1.42–4.36). Discussion: Ethnoracial and regional differences in risk factors and causes of stroke at young age provide an understanding of ethnic and racial and regional differences in incidence of ischemic stroke. Our results also highlight the dissimilarities in outcome after stroke in young adults that exist between LMICs and HICs, which should serve as call to action to improve health care facilities in LMICs.